Cutaneous manifestation in children with HIV/AIDS - Seyed Naser Emadi; Shrikank Mansukhlal Bhatt; James Machoki M'Imunya; Andrew Juma Suleh; Seyed Reza Raeeskarami; Mohammad Sadegh Rezai; Mohammad Reza Navaeifar (Mazandaran University of Medical Sciences, 2014)
The most recent studies have explained almost 2.3 million children are affected with HIV up to the end of 2009. Sub-Saharan Africa is the main region affected by AIDS compare to other parts of the world. Despite providing competent healthcare services to prevent mother-to-child transmission as a main way of infection to a newborn, an estimated 370,000 children were newly infected to HIV in 2009. Skin disorders are common and may even be the first manifestation of HIV in children.The most common skin illnesses are classified in four categories; infectious, inflammatory, neoplastic, and drug related (Highly Active Antiretroviral Therapy). In addition, unusual anatomical sites, disseminated skin lesions, increased frequency and severity, unexplained clinical presentation, rapid onset, and finally treatment failure may be the other specified skin conditions in HIV/AIDS children. CD4 count and viral load are two basic factors playing an important role in terms of type and severity of skin illness. The aim of this review was to show the common and crucial cutaneous findings among HIV/AIDS children via published articles with the same subject.